Computational Fluid Dynamic Analysis in Dam Spillway Due to Sector Gate Opening - Hassan N.H.; Zawawi M.H.; Radzi M.R.M. (Springer Science and Business Media Deutschland GmbH, 2023)
Computational fluid dynamics; Dams; Hydraulic jump; Spillways; Computational fluid dynamic; Computational fluid dynamics modeling; Dam spillway; Fluid dynamic analysis; Fluid-dynamic analysis; Fluid-dynamics; Gate openings; High velocity; Hydraulic parameters; Paper analysis; Velocity